2017
DOI: 10.1021/acssuschemeng.6b03209
|View full text |Cite
|
Sign up to set email alerts
|

Decarboxylative Coupling Strategy To Afford N-Heterocycles Driven by Silica-Nanosphere-Embedded Copper Oxide (Cu@SiO2-NS)

Abstract: An environmentally benign and surfactant-free method was developed for the preparation of porous silica nanospheres (SiO2 NS) from the hydrolysis of tetraethoxyorthosilicate (TEOS), using corn starch as a sacrificial template. The stabilization of malachite on SiO2 NS, followed by calcination at 600 °C, afforded silica-nanosphere-embedded copper oxide (Cu@SiO2-NS). The obtained Cu@SiO2-NS was found to be a versatile nanocatalyst for the decarboxylative coupling strategies to afford aromatic or aliphatic N-hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…As shown in Figure , the binding energies of Cu 2p in the fresh (Figure a) and recovered catalyst (Figure b) were measured to be 932.8 eV and 953.1 eV. These results indicated that the presence of Cu II species in both freshly prepared and recovered catalyst …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As shown in Figure , the binding energies of Cu 2p in the fresh (Figure a) and recovered catalyst (Figure b) were measured to be 932.8 eV and 953.1 eV. These results indicated that the presence of Cu II species in both freshly prepared and recovered catalyst …”
Section: Resultsmentioning
confidence: 99%
“…These results indicated that the presence of Cu II species in both freshly prepared and recovered catalyst. [19][20][21]44] The SEM images of PAA/PVC and Cu II @PAA/PVC shown in Figure 4 were recorded at low (200 nm) and high magnifications (100 nm) for easy clarity and comparison. The visible rough surface with porous can be observed for PAA/PVC hybrid fibers (image a, and b).…”
Section: Characterization Of the Mesoporous Cu II @Paa/pvc Hybrid Fmentioning
confidence: 99%
See 1 more Smart Citation
“…Rawat et al. reported a green and sustainable approach for the decarboxylative tandem coupling of proline 205 , 3‐nitrobenzaldehyde 451 , and phenylacetylene or phenyl propionic acid 452 to afford aliphatic nitrogen heterocycles such as 1‐benzyl‐2‐(phenylethynyl)pyrrolidine 453 using a Cu nanocatalyst (Cu@SiO 2 ‐NS) (Scheme ) …”
Section: Miscellaneous Reactionsmentioning
confidence: 99%
“…Transition metal-catalyzed decarboxylative coupling reaction provides an ecofriendly pathway for C–C or C–heteroatom bond formation due to in situ formation of organometallic species. This involves relatively neutral conditions and eliminates expensive and toxic organometallic reagents. , Various decarboxylative Csp 3 –Csp 3 , Csp 3 –Csp 2 , and Csp 3 –Csp couplings have been reported to synthesize a wide range of value-added chemicals including propargylamines, biaryls, , 2-alkynylbuta-1,3-dienes, 1,4-diamino-2-butynes, 1,2,3-triazoles, etc. Recently, we reported decarboxylative A3 and KA2 coupling strategies for one-pot multicomponent reactions to afford a wide range of propargylamines and C1-alkynylation of tetrahydroisoquinolines and N-heterocycles using CuO@Fe 2 O 3 MNPs and Cu@SiO 2 –NS as recyclable nanocatalysts, respectively. , To date, there are very few reports describing the decarboxylative tandem coupling among proline, aldehydes, and alkynes using Cu-salts as homogeneous catalysts. There is a need to develop efficient nanocatalysts for these decarboxylative tandem coupling reactions under green and sustainable conditions. In this context, we herein report RGO@CuO nanocatalyzed decarboxylative tandem coupling among proline, aldehydes, and alkynes with equimolar ratios yielding a wide range of substituted pyrrolidines with minimum waste generation and high reaction mass efficiency under green reaction conditions (Scheme ).…”
Section: Introductionmentioning
confidence: 99%